2021
DOI: 10.1155/2021/5555619
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Low Levels of α-1 Antitrypsin and Elevation of Neutrophil to Lymphocyte Ratio with Higher Mortality in Severe COVID-19 Patients

Abstract: Background. Variations in COVID-19 prevalence, severity, and mortality rate remain ambiguous. Genetic or individual differences in immune response may be an explanation. Moreover, hyperinflammation and dysregulated immune response are involved in the etiology of severe forms of COVID-19. Therefore, the aim of the present study was to analyze serum alpha-1 antitrypsin (AAT) levels, as an acute-phase plasma protein with immunomodulatory effect and neutrophil to lymphocyte ratio (NLR) as a marker of inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Given our findings and the previously mentioned studies showing that those with AAT deficiency are more predisposed to severe disease and death from COVID-19, it is reasonable to surmise that AAT augmentation in those with severe AAT deficiency would be beneficial against COVID-19. Nevertheless, even in the absence of frank AAT deficiency, the AAT response to a systemic infection may be inadequate as has been shown for hospitalized COVID-19 patients 40 and among millions with certain heterozygous AAT mutations 41 . This possibility leads to the question of whether AAT supplementation would be beneficial even in those without frank AAT deficiency?…”
Section: Discussionmentioning
confidence: 99%
“…Given our findings and the previously mentioned studies showing that those with AAT deficiency are more predisposed to severe disease and death from COVID-19, it is reasonable to surmise that AAT augmentation in those with severe AAT deficiency would be beneficial against COVID-19. Nevertheless, even in the absence of frank AAT deficiency, the AAT response to a systemic infection may be inadequate as has been shown for hospitalized COVID-19 patients 40 and among millions with certain heterozygous AAT mutations 41 . This possibility leads to the question of whether AAT supplementation would be beneficial even in those without frank AAT deficiency?…”
Section: Discussionmentioning
confidence: 99%
“…AAT plasma levels can normally increase 3-to 5-fold in the course of systemic inflammation and/or infection, however, AAT was observed to be present at low levels in severe cases of COVID-19 [237]. In agreement with these findings, Vianello and Braccioni [238] showed that, in Italy, there was a geographic co-localization between individuals with AAT deficiency and the number of COVID-19 cases.…”
Section: Secretory Leucocyte Protease Inhibitor (Slpi)mentioning
confidence: 64%
“…In agreement with these findings, Vianello and Braccioni [238] showed that, in Italy, there was a geographic co-localization between individuals with AAT deficiency and the number of COVID-19 cases. Interestingly, AAT serum levels can be modulated by genetic variants as well as by cigarette exposure, oxidative stress and pollution, and these changes may have a significant relevance in lowering the protective role of AAT during COVID-19 [234,237]. Since AAT irreversibly inhibits serine proteases and elastases, but may also exert anti-viral, anti-TMPRSS-2, anti-inflammatory, anti-thrombin, anti-NETs and antiapoptotic activities, AAT represents an additional candidate for the treatment of COVID-19 [234].…”
Section: Secretory Leucocyte Protease Inhibitor (Slpi)mentioning
confidence: 99%
“…Indeed, several studies pointed to a tentative link between lower blood AAT levels and severe Covid-19, suggesting that AAT deficiency contributes to Covid-19 fatalities (Faria et al, 2021;Ferrarotti et al, 2021;Shapira et al, 2020;Shimi et al, 2021;Vianello & Braccioni, 2020). Indeed, bioengineered AAT, which is approved for treating lung inflammation in AAT deficient individuals, was proposed as potential therapeutic for Covid-19 (Marzouk et al, 2021;Yang et al, 2020;Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced expression of SERPINA1 , coding for alpha‐1 antitrypsin (AAT), observed following chronic d ‐galactose treatment, also suggests higher SARS‐CoV‐2 infection load: AAT readily inhibits TMPRSS2 (Azouz et al, 2021; Wettstein et al, 2021), which is essential for priming SARS‐CoV‐2 for cell entry (Azouz et al, 2021; Hoffmann et al, 2020). Indeed, several studies pointed to a tentative link between lower blood AAT levels and severe Covid‐19, suggesting that AAT deficiency contributes to Covid‐19 fatalities (Faria et al, 2021; Ferrarotti et al, 2021; Shapira et al, 2020; Shimi et al, 2021; Vianello & Braccioni, 2020). Indeed, bioengineered AAT, which is approved for treating lung inflammation in AAT deficient individuals, was proposed as potential therapeutic for Covid‐19 (Marzouk et al, 2021; Yang et al, 2020; Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%